Assessment of organizational management capability and employee’ satisfaction at select maternity hospitals in Ulaanbaatar - Tseleejav, Batbold; Luvsansambuu, Tumurbaatar; Luvsan, Munkh-Erdene (Proceedings of the Mongolian Academy of Sciences, 2020)
Healthcare organizations are implementing quality management system by forming legal entity, by carrying out administrative structural changes and developing healthcare organization’s structure, set-up, functional standards, clinical guideline, rules and employee´ moral principles. Introduction of accreditation system into healthcare organizations is becoming an accepted standard, however, healthcare paradigm shift outcome is insufficient. In this connection, researchers, citizens and policy makers are speaking out that the quality of and access to healthcare service is getting worse than before. Management capability index presents management assessment by score, assesses outcome of organizational functions and makes it possible to measure management capability. This study was performed at the Amgalan maternity hospital, Urguu maternity hospital and Khuree maternity hospital between July 2019 and September 2019 and cross-sectional study method was used. The study involved 480 employees of above-mentioned hospitals. We used 9 chapter and 90 criteria that were used in more than 30 Mongolian Public (i.e., Governmental) Organizations for capability assessment to determine management capability index of the maternity hospitals. Organization management capabilities, as an organizational goal and task, leadership skill in an organization, appropriate structure and set-up, organization’s incentive and motivation leverage schemes, organization’s relationship and collaboration, organizational behavior and culture, resource utilization, knowledge and innovation, organizational productivity, quality and performance were included in the questionnaire. Organizations capability index was calculated with a score point of 1 to 5 for each question. A total 480 employees, including 220 from the Urguu maternity Hospital, 125 from the Khuree maternity hospital and 135 from the Amgalan maternity hospital were included in this study. When responses to the question of management capability were according to duties and functions, not much difference was observed among the three hospitals, but when the responses were compared with that provided by doctors, nurses, obstetricians and other medical staff, a 1.8 percentage higher point was given by the administrative and service staff. Regression analysis showed strong relation between management capability assessment of doctors, nurses, obstetricians and other employee of the select hospitals (p<0.001 and R=0.89). Organizational management capabilities of Urguu and Khuree Maternity Hospitals, which have not yet introduced quality management system, are different from the Amgalan maternity hospital’s organizational management capability (p=.000). Doctors, obstetricians, nurses and other employee’ assessed organizational management capability by 73.5 percent respectively. There is a positive correlation ship between organizational capability and employee satisfaction. Better and higher management capability of an organization results in higher employee satisfaction.